Medicalizing Me Softly: An Autoethnography of Refusal - Amm,Han (2022)
This autoethnographic study explores intra-community discursive boundary constructions around the category of transgender articulated by truscum trans men on Reddit. It does so through reflections on how the author negotiates the medical model of trans, his own gender identity, the medico-juridical interlock governing access to trans healthcare and trans livability, and tensions of closeness/distance to those they interview. Semi-structured and email interviews with truscum trans men are used to examine participants’ negotiations of the medical model, definitional disputes over transgender/nonbinary, medical transition technologies, and their subject position as truscum. Through the lens of transnormativity, poststructuralism and the medical model, the construction of the transsexual subject is described. The study finds truscum trans men on Reddit use the category of transsexual strategically to construct sameness in opposition to what is perceived as difference of non-normative/nonbinary trans identities, and therefore, as not trans. Truscum is articulated as a response to the medical model and a subject position entailing an affective/emotional dimension in providing care and community. Truscum subreddits, in building echo chambers, serve the function of simultaneously detaching from and articulating a critique of dominant trans discourse. A metaphysics of refusal, aided by the concept of liminality, is proposed, in which the author refuses to stabilize the category of transgender in tension with their interview participants’ conceptualization of transgender.
Keywords: transmedicalism; truscum; transnormativity; nonbinary; autoethnography; refusal; liminality